Perception of Relationship Marketing in Commercial Bank: Empirical Evidence from Kathmandu Val - Dhakal, Krishna; Khatiwada, Anil Prasad; Devkota, Niranjan; Basyal, Devid Kumar; Mahato, Surendra; Paudel, Udaya Raj; Upretee, Sahadeb; Bhattarai, Ujjwal (The Journal of Economic Concerns, 2022)
Network based relationship marketing in commercial bank continues to be crucial, where success or failure is directly related to staff. Only when quality of relationship is stable and engaged, customer satisfaction and customer engagement will be connected with discovering new solutions for existing and future markets to sell the banking product. Therefore, this study tries to understand perception of relationship marketing in commercial bank of Kathmandu Valley. The explanatory research design was used with the essence of network-based theory. The data was evaluated quantitatively by using descriptive and inferential analysis by using structured questionnaire method using KOBO toolbox. SEM was applied to analyze the relationship from sample of 204 responses in Kathmandu Valley. Findings reveal that banks are aware about the relationship marketing practices and depict that there is significant relationship between bonding, trust and communication to customer satisfaction. Therefore, banking workers feel that trust, bonding, communication, shared values and empathy are critical factors in relationship marketing.